Postharvest phytosanitary disinfestation strategies using thermal and atmospheric stress: commodity and insect tolerances - Smit, Renate (Stellenbosch : Stellenbosch University, 2019)
Thesis (PhDAgric)--Stellenbosch University, 2019.